Angiotensin Receptors Heterodimerization and Trafficking: How Much Do They Influence Their Biological Function? - Rukavina Mikusic, Natalia L.; Silva, Mauro G.; Pineda, Angélica M.; Gironacci, Mariela M. (Frontiers in Pharmacology, 2020)
G-protein-coupled receptors (GPCRs) are targets for ~ 30% of drugs currently on the market and constitute the largest and most structurally diverse family of transmembrane signaling proteins, with almost 1000 members identified in the human genome. Upon agonist stimulation, GPCRs are internalized and trafficked inside the cell: they may be targeted to different organelles, or recycled back to the plasma membrane or be degraded. Once inside the cell, the receptors may initiate other signaling pathways leading to different biological responses. GPCRs' biological function may also be influenced by interaction with other receptors. Thus, the ultimate cellular response may depend not only on the activation of the receptor from the plasma membrane, but also from receptor trafficking and/or the interaction with other receptors. This review is focused on angiotensin receptors and how their biological function is influenced by trafficking and interaction with others receptors.